Recruiting `hard to reach? parents for health promotion research: experiences from a qualitative study - Hayes, Catherine (My University, 2021)
Objective: Marginalised populations are less likely to take part in health research, and are sometimes considered ‘easy to ignore’. We aimed to describe our approach and results of recruiting parents who experience disadvantage, for focus groups exploring infant feeding on the island of Ireland. Upon receiving ethical approval, we implemented recruitment strategies that included building rapport with community organisations through existing networks, tar‑ geting specific organisations with information about our aims, and utilising social media groups for parents. Results: We approached 74 organisations of which 17 helped with recruitment. We recruited 86 parents/carers (one male) for 19 focus groups (15 urban/4 rural). Seventy two percent met at the eligibility criteria. Most participants were recruited through organisations (91%), and the remainder on social media (9%). Recruitment barriers included multiple steps, research fatigue, or uncertainty around expectations. Factors such as building rapport, simplifying the recruitment process and being flexible with procedures were facilitators. Despite comprehensive, multi‑pronged approaches, the most marginalised parents may not have been reached. Further alternative recruitment strategies are required for recruiting fathers, rural populations, or those without the capacity or opportunity to engage with local services.
PUBLISHED
Keywords: Social Determinants of Health; Research recruitment; Health promotion research; Parenting; Marginalized groups; Hidden populations; Seldom heard voices; Qualitative research; Inclusive Society